Seven new species of Meta C.L. Koch, 1836 (Araneae, Tetragnathidae) from Southwest China - Wang, Lu-Yu; Irfan, Muhammad; Chen, Hui-Ming; Zhang, Zhi-Sheng (European Journal of Taxonomy, 2022)
Seven new species of the genus Meta C.L. Koch, 1836 from Southwest China are described here: M. bowo sp. nov. (♂♀), M. cona sp. nov. (♂♀), M. gyirong sp. nov. (♂), M. hongyuan sp. nov. (♂♀), M. tibet sp. nov. (♂♀), M. wanglang sp. nov. (♂♀) and M. weining sp. nov. (♂♀). Detailed descriptions, photos of somatic features and copulatory organs as well as line drawings, comparisons with closely related species, and a distribution map are provided.